New molecular reporters for rapid protein folding assays. - Stéphanie Cabantous; Yvonne Rogers; Thomas C Terwilliger; Geoffrey S Waldo (PLoS ONE)
The GFP folding reporter assay uses a C-terminal GFP fusion to report on the folding success of upstream fused polypeptides. The GFP folding assay is widely-used for screening protein variants with improved folding and solubility, but truncation artifacts may arise during evolution, i.e. from de novo internal ribosome entry sites. One way to reduce such artifacts would be to insert target genes within the scaffolding of GFP circular permuted variants. Circular permutants of fluorescent proteins often misfold and are non-fluorescent, and do not readily tolerate fused polypeptides within the fluorescent protein scaffolding. To overcome these limitations, and to increase the dynamic range for reporting on protein misfolding, we have created eight GFP insertion reporters with different sensitivities to protein misfolding using chimeras of two previously described GFP variants, the GFP folding reporter and the robustly-folding "superfolder" GFP. We applied this technology to engineer soluble variants of Rv0113, a protein from Mycobacterium tuberculosis initially expressed as inclusion bodies in Escherichia coli. Using GFP insertion reporters with increasing stringency for each cycle of mutagenesis and selection led to a variant that produced large amounts of soluble protein at 37 degrees C in Escherichia coli. The new reporter constructs discriminate against truncation artifacts previously isolated during directed evolution of Rv0113 using the original C-terminal GFP folding reporter. Using GFP insertion reporters with variable stringency should prove useful for engineering protein variants with improved folding and solubility, while reducing the number of artifacts arising from internal cryptic ribosome initiation sites.